Use of everolimus following kidney transplantation during pregnancy: A case report and systematic review - Pony Yee-Chee Chai; Chih Lin; Chuan-Chi Kao; Li-Mei Lin; Yi-Hua Chen; Chiao-Yin Sun (Elsevier, 2023)
Objective: There is limited safety data on the use of everolimus during pregnancy. In this study, we present the maternal and neonatal outcomes of everolimus used throughout the course of pregnancy and conducted a systematic review of reports of everolimus use after organ transplantation during pregnancy. Case report: A woman with type 1 diabetes who underwent kidney transplantation was treated with tacrolimus, everolimus, and prednisolone. Two years later, she became pregnant. At 27 weeks of gestation, an emergent cesarean delivery was performed owing to severe preeclampsia and fetal distress. No congenital malformation was noted in the baby at a corrected age of 4 months, and the maternal renal function remained stable. Conclusion: Our systematic review did not identify evidence of teratogenicity in babies exposed to everolimus as an immunosuppressant after transplantation. To better assess the risk of exposure to everolimus during pregnancy, all cases of new pregnancies occurring in transplant recipients receiving treatment with mammalian target of rapamycin inhibitor inhibitors should be reported.